A sieve-conducted two-syringe-based pressurized liquid-phase microextraction for the determination of indium by slotted quartz tube-flame atomic absorption spectrometry - Unutkan, Tugce; Borahan, Tulay; Girgin, Ayca; Bakirdere, Sezgin (SPRINGER, 2020)
In this study, a new liquid-phase microextraction method termed sieve-conducted two-syringe-based pressurized liquid-phase microextraction (SCTS-PLPME) was developed as a preconcentration tool for indium. Here, two syringes were connected to each other by an apparatus to produce an environment subject to pressure. The pressure created between the two syringes by simultaneous movements of the syringe plungers (to and fro) generated an efficient dispersion and this eliminated the need for dispersive solvents. Determination of indium after preconcentration was carried out with a slotted quartz tube attached flame atomic absorption spectrometer (SQT-FAAS). The detection limit (LOD) and quantification limit (LOQ) of the developed method were calculated as 19.2 and 72.2 mu g L-1, respectively. The reliability and accuracy of the developed method was tested by performing recovery studies on lake water spiked at different concentrations and the obtained percent recoveries were between 101.2 and 106.9%.
Keywords: Syringe; Flame atomic absorption spectrometry; Indium; Liquid-phase microextraction; PRECONCENTRATION; EXTRACTION; LEAD; Environmental Sciences & Ecology